Workshop The Artificial Intelligence in the Era of Flat Earth Hoaxes 2.0 - Lubis, Muharman; Fansyah, Egi Al (Jurnal Pengabdian Bakti Akademisi, 2025)
The rapid development of Artificial Intelligence (AI) has transformed the way humans produce and disseminate information. On one hand, AI expands access to knowledge; on the other, it amplifies the spread of hoaxes and disinformation, blurring the line between fact and fabrication. This paradox became the central theme of the community service event titled Workshop on The Artificial Intelligence in the Era of Flat Earth Hoaxes 2.0,which explored AIs dual role as both a creator and a countermeasure of digital hoaxes.This activity adopted a service-learning approach, engaging 70 participants consisting of university students and educators through interactive discussions, case analyses,and pre-test and post-test evaluations. The results indicated an average improvement of 6.5% across three key dimensions of information literacy: hoax literacy, AI literacy, and information ethics literacy, with the highest increase observed in the ethical dimension. These findings affirm that exposure to ethical frameworks and critical reflection can foster moral awareness and a sense of responsibility among participants in their interactionswithin digital spaces.Overall, this activity underscores the importance of integrating AI ethics literacy into public education to strengthen societys resilience against digital manipulation. This initiative supports the achievement of SDG 4 (Quality Education), SDG 9 (Industry, Innovation, andInfrastructure), and SDG 16 (Peace, Justice, and Strong Institutions) through the enhancement of digital literacy, information ethics, and responsible communication in theera of artificial intelligence.